Pengaruh Peer Teaching Model Dalam Permainan Bola Voli Terhadap Motivasi Belajar Siswa Sekolah Menengah Pertama - Santika, Bela; Faridah, Ai; Permana, Dian (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
the purpose of this research is to find out, analyze and identify the influence of the Peer Teaching model in the game of volleyball on the learning motivation of class VII students at SMP Negeri 4 Klari. To answer the formulated research problem, the author uses a quantitative approach with experimental methods. This research was conducted at SMP Negeri 4 Klari by taking two classes as research samples, namely VII G with a total of 40 students, and VII B with a total of 37 students out of 512 students with a total of 13 classes in VII class. There are three stages in this research, namely pretest, treatment, and posttest. A pretest was carried out in both classes to determine students' initial cooperation abilities before receiving treatment. After the pretest, the researcher provided treatment, namely eight meetings in the experimental class and control class with the tutor teacher, in the experimental research class using the Peer Teaching model while in the control class the tutor teacher used the conventional learning model (Direct Instruction). After being given treatment, the researcher then conducted a posttest in both classes to find out whether there was an influence of the Peer Teaching model in the experimental class. Analysis of Covariance (ANCOVA) was used to analyze the data. The esults of this research prove that the Peer Teaching model in volleyball games has an influence on junior high school students' learning motivation with the following explanation: 1). The application of the Peer Teaching model in volleyball games has an effect on students' learning motivation. 2). The application of the conventional learning model (Direct Instruction) in the game of volleyball has an effect on students' learning motivation. 3). The application of the Peer Teaching model shows a different influence with a more effective influence than the conventional learning model (Direct Instruction) in the game of volleyball on students' learning motivation. Therefore, through the Peer Teaching model, it is hoped that it can help improve students' cooperative attitudes in their daily lives so that they can contribute to the development of character education in Indonesia.